2004
DOI: 10.1038/sj.bjc.6601881
|View full text |Cite
|
Sign up to set email alerts
|

HER2 expression in breast cancer primary tumours and corresponding metastases. Original data and literature review

Abstract: The aim of this study was to evaluate whether the HER2 expression in breast cancer is retained in metastases. The HER2 expression in primary tumours and the corresponding lymph node metastases were evaluated in parallel samples from 47 patients. The HercepTest was used for immunohistochemical analyses of HER2 overexpression in all cases. CISH/FISH was used for analysis of gene amplification in some cases. HER2 overexpression (HER2-scores 2 þ or 3 þ ) was found in 55% of both the primary tumours and of the lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
138
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(148 citation statements)
references
References 34 publications
(38 reference statements)
6
138
0
4
Order By: Relevance
“…This result is in accordance with those concerning visceral metastases and local and regional metastases (Barnes et al, 1988;Niehans et al, 1993;Masood and Bui, 2000;Simon et al, 2001;Gancberg et al, 2002;Vincent-Salomon et al, 2002;Carlsson et al, 2004). Recently, in a meta-analysis of the published data concerning HER2 status stability among primaries and metastases, Carlsson et al (2004) confirmed that there was no drastic modification in HER2 status between primary tumours and their locoregional lymph node metastases and their distant visceral metastases.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This result is in accordance with those concerning visceral metastases and local and regional metastases (Barnes et al, 1988;Niehans et al, 1993;Masood and Bui, 2000;Simon et al, 2001;Gancberg et al, 2002;Vincent-Salomon et al, 2002;Carlsson et al, 2004). Recently, in a meta-analysis of the published data concerning HER2 status stability among primaries and metastases, Carlsson et al (2004) confirmed that there was no drastic modification in HER2 status between primary tumours and their locoregional lymph node metastases and their distant visceral metastases.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, in a meta-analysis of the published data concerning HER2 status stability among primaries and metastases, Carlsson et al (2004) confirmed that there was no drastic modification in HER2 status between primary tumours and their locoregional lymph node metastases and their distant visceral metastases.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…HER-2 oncogene is located on the long arm of chromosome 17 (17q12-q21) (Owens et al, 2004) and plays a role in the pathogenesis of a significant number of human tumours. Approximately 20-30% of breast carcinomas and probably a higher percentage in the more malignant subgroups that form lymph node or distant metastases show altered HER-2 expression (Eccles, 2002;Carlsson et al, 2004). This is manifested as gene amplification and/or protein overexpression (Ross and Fletcher, 1999).…”
Section: Erbb2/her-2 (Her-2/neu Neu Ngl Her-2 Tkr1 Cd340mentioning
confidence: 99%
“…11 Earlier studies exclusively used HercepTest to assess the maintenance of HER-2/neu genotype in metastatic lesions and found it concordant in case of lymph node, liver and lung metastases. [12][13][14][15][16] Recent reports provided evidence that the HER-2/neu genotype of BRC may change in the metastases: loss of HER-2/neu expression was reported in one case in pleural metastases, 17 while loss of HER-2/neu amplification was found in 21%, but appearance of HER-2/neu amplification was even more frequent in visceral metastases (30%). 18 Our aim was to analyze the HER-2/neu status of bone metastasis compared to the primary tumor in a larger cohort of BRC cases.…”
Section: Introductionmentioning
confidence: 99%